PERKEMBANGAN SENI KRIYA DI TENGAH PERUBAHAN MASYARAKAT - I Ketut Sunarya (Imaji, 2006)
As human creation, fine art is a human or cultural fact as well as asemiotic fact. A fine art has a specific existence that distinguishes it from otherhuman facts, that is an existence feature inseparable from the balanceconsideration between reason and feeling. Therefore, despite an artist' freedomin actualizing and appreciating what he wants to express, he needs to hold thebasic principle of fine art, namely its closeness to human life. The basicconcept of the art is as a starting point and the artist' mirror to reflect his duty tokeep its potential of typical areas and to open new art horizon in creating a newclassification system. This is a real step expected to determine the art's positionand bargaining value in this rapid growing era.Key words: fine art, and social changes